Ageing Population Policy in Indonesia: A Narrative Review - Mangunsong, Farma; Jirapramukpitak, Tawanchai; Hastuti, Sari (Jurnal Kebijakan Kesehatan Indonesia, 2025)
The percentage of elderly people in Indonesia has surpassed 10%, drawing attention to the specific needs of this demographic. While physical decline is a natural part of ageing, additional needs often emerge as individuals grow older. Ageing is associated with increased demand for healthcare services, financial instability, and a rising elderly dependency ratio. This study analyses elderly care policies in Indonesia, evaluates existing healthcare systems and social support, and compares them with models from several other countries. A narrative review approach was used, incorporating thematic analysis of literature, policy documents, research reports, and statistical reports. The study finds that although various initiatives have been implemented, their execution remains fragmented. Challenges are compounded by unintegrated healthcare services, limited infrastructure in remote areas, insufficient financial assistance, and the absence of a long-term care system. Compared to other countries with more integrated elderly healthcare services, Indonesia needs to improve support for this vulnerable group. The study recommends the development of an integrated national policy, improved access to financial assistance, strengthened community-based healthcare services, and long-term funding for elderly care. Further research is needed to assess the effectiveness of existing policies, the role of informal caregivers, and sustainable financing mechanisms to enhance elderly care systems in Indonesia.